Effects of tributyrin on the growth performance, survival, tolerance to hypoxic stress, and nutrient digestibility of Pacific white shrimp, Litopenaeus vannamei, fed different levels of soybean meal - Rairat, Tirawat; Phansawat, Putsucha; Keetanon, Arunothai; Kachapol, Parattagorn; Kumphaphat, Sunisa; Kitsanayanyong, Lalitphan; Chou, Chi‐Chung; Chuchird, Niti (Journal of the World Aquaculture Society, 2023)
The study aimed to evaluate the effect of tributyrin on the growth performance, survival, hypoxia tolerance, and nutrient digestibility of Pacific white shrimp fed 25% and 50% soybean meal (SBM) diets. Six experimental diets were formulated: (1) 25% SBM without tributyrin; (2) 25% SBM with 0.05% tributyrin; (3) 25% SBM with 0.1% tributyrin; (4) 50% SBM without tributyrin; (5) 50% SBM with 0.05% tributyrin; and (6) 50% SBM with 0.1% tributyrin. The shrimp were fed the experimental diets daily for 10 weeks. Tributyrin supplementation at 0.1% diet significantly improved the weight gain of shrimp that fed 25% SBM but not the other groups. Nevertheless, shrimp that fed tributyrin had significant improvement in survival rate at both SBM levels. Significant reductions in Vibrio spp. counts in the hepatopancreas and intestine were also evident in all tributyrin‐fed groups. In addition, 0.1% tributyrin in both SBM levels significantly enhanced the shrimp tolerance to hypoxia. Lastly, the digestibilities were generally unaffected by the tributyrin except only for the lipid digestibility of the 0.1% tributyrin in 25% SBM group, which showed a significant increase. Overall, tributyrin was proven beneficial for the shrimp's health, especially for those fed diet with a moderate level of SBM (25%).